(untitled) (Anwer Khan Modern Medical College Journal, 2017)
Sleep disorders and sleeping difficulty are poorly-addressed problems of aging. Research has shown that as many as 50% of older adults complain about difficulty in initiating or maintaining sleep. Elderly with varieties of sleep complaints are differentially affected by ’age-related cognitive decline’. Normal developmental processes have been affected with changes in sleep, which can be further compromised by sleep disturbances secondary to medical or psychiatric diseases such as chronic pain, depression, dementia or age-related primary sleep disorders (e.g., sleep disordered breathing and periodic limb movements during sleep), or certain combinations of these high-risk factors. Sleep serves as a protective mechanism to keep the organism out of danger; therefore, it is imperative to consider sleep disorders for quality life. The evaluation of these disorders is discussed in this review. Anwer Khan Modern Medical College Journal Vol. 7, No. 1: Jan 2016, P 45-49